Sources And History of Housing Policy in Uzbekistan (1991-2021) (Zien Journal of Social Sciences and Humanities, 2021)
Today, housing policy plays a key role in the economic and social spheres of the world. In recent years, the growth of the world's population and, conversely, the decline in land for habitation have necessitated the efficient use of land. On the other hand, this housing policy is not only related to construction work, but also to the urban planning policy of the states. It is as a result of this policy that the stages of development or decline of housing construction can be observed. In addition, housing issues are an area that is also measured by demographic and migration conditions. By studying the impact of housing policy on socio-economic relations or, conversely, their impact on housing policy, it is possible to identify certain data that will help to develop urban planning.